Sistem Temu Kembali Koleksi di Perpustakaan PT PLN (Persero) Wilayah Sumatera Barat - Akhri, Jumaidi; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This paper discusses the Gathering System Back Collection In Library PT. PLN (Persero) West Sumatra. This study aimed to determine: (1) How retrieval system in the library collection PT. PLN (Persero) West Sumatra. (2) obstacles encountered in the retrieval system in the Library collection PT. PLN (Persero) West Sumatra.Data were collected through observation and interviews to the librarian at the Library of PT. PLN (Persero) Sumaetra Western Region. Based on data analysis concluded the following: (1) retrieval system library materials in the Library PT. PLN (Persero) West Sumatra is not optimal, it can be seen in the absence of the use of the card catalog that is useful to facilitate retrieval. (2) The constraints found in the retrieval library collection in the Library PT. PLN (Persero) West Sumatra, namely: first, the lack of tool retrieval of library materials in the library PT. PLN (Persero) West Sumatra. Second, the quality of human resources is still low, so that the quality of human resources in the Library PT. PLN (Persero) West Sumatra increased need to be developed by: (a) librarians can participate in professional activities (participating in seminars / workshops), (b) Librarians have lots of reading, lots of reading will be able to expand their knowledge, improve skills, improve skills and keep abreast of science Keywords: retrieval system; library collection